(3JMaI GdfLHG HefGbH GdZQHGs - (3eMeO GdefTGhjs
(3ChdgG (B:s
(3GdMeO ddg GdPi Ye GdHdGO SYJg hGQaGOg hHYO agPg QSGdI dWjaI JJVef ahGjO TQjaI ef cJGH GdZQHG ddEeGe GdGLQg s
(3BNQgG (B:s
(3hef fcO GdOfjG Ydi GdMQ Cf jQi YOhdg eG ef UOGbJg HO GfJgi hgPG BNQ eG JjSQ JYdjbg hUdi Gddg Ydi SjOfG eMeO hBdg hUMHg hSde hMSHfG Gddg hfYe Gdhcjd s
(3HgG fXGe GdJYbjHIs
(3cJHJ GdeNWhW ai MjGI GdeUfas
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK s
(3eUOQ GbJfGA GdCUd (B:s
(3GdRjOGfjI ef GdNRGfI GdedcjI HeOjfI GdQHGW (B(3761) s
Keywords: (3GdJGQjNs